Estimation of Nutritional and Mineral Contents of Eleusine coracana and Echinochloa frumentacea – Two Edible Wild Crops of India - Chandra, Subhash; Saklani, Sarla; Semwal, Ruchi B.; Semwal, Deepak K. (Current Nutrition & Food Science, 2019)
Background: Barnyard millet is rich in protein, iron, calcium, phosphorus, fibre and vitamin content whereas finger millet is used in regular food and considered to be more nutritious than rice. Objective: The aim of this research was to develop new food supplements with potential pharmacological activity from readily accessed natural products. Methods: In the present study, we investigated the nutritional and mineral profile of the extracts of Eleusine coracana (L.) Gaertn. and Echinochloa frumentacea Link seeds. The extraction process involved fractionation with various solvents whereas the estimation of nutrients and minerals was done using AOAC method and ICPMS techniques. Results: The levels of crude protein, carbohydrates, crude fibre and ash content in E. coracana seeds were found to 7.30%, 68.10%, 3.60% and 8.50%, respectively whereas 2.87%, 80.93%, 5.80% and 5.30%, respectively were measured in the seeds of E. frumentacea. Conclusion: The seeds of E. coracana and E. frumentacea were found as highly medicinal and nutritional due to the presence of vitamins, minerals and other needful nutrients.
Keywords: koda